121 Advances with Exogenous Dietary Enzymes to Reduce Diet Cost and Improve Viability in Growing Pigs. (10th April 2018) - Boyd, R D; Zier-Rush, C E; van Heugten, E
Abstract: Exogenous dietary enzymes were envisioned as a means to reduce diet cost and to degrade anti-nutrients. The feed cost mitigation tactic was initiated by the NPB Animal Science committee in 2012 to better deliver on that vision. Top priorities involved: (1) Increase nutrient extraction (enzymes, processing), (2) Identify enzymes to improve use of low-energy ingredients (low starch, high NDF), (3) Identify functional ingredients to mitigate disease impact on viability, growth and FCE. Twenty-three projects were funded by the NPB from 2012-2016. Undergirding this public effort is the example of phytase, a landmark advance in animal nutrition science. Feed enzyme effectiveness, beyond phytase, has been more easily demonstrated in Poultry than pigs. Nevertheless, several opportunities emerged: (1) amino acid and energy release with high levels of phytase; (2) phytate destruction, using a phytase super-dose, reduced diet cost by allowing greater SBM by preventing associated stool looseness; (3) a new frontier was discovered when Xylanase was shown to improve finish pig viability; (4) Improved energy release from high NDF, low starch ingredients was proven possible, but difficult. Recent studies with a phytase super-dose (e.g. 2500 FTU/kg) showed improved growth and FCE in weaned pigs. A recent report (Moran et al., 2018) suggests that the extra-phosphoric effects may be partially explained by the liberation of inositol, through near complete dephosphorylation of phytate. Blood inositol was increased and had a metabolic impact in piglets immediately after weaning. This suggests that inositol may be conditionally essential for young pigs during the stress of weaning; an ancillary benefit attributed to inositol being to stress response. It has been difficult to demonstrate release of energy by Xylanase, in finish pigs, but an unanticipated benefit emerged in improved (40%) viability (Zier-Rush et al., 2015). Technologies that improve livability and ability to thrive (fewer cull pigs) have high economic impact. Xylanases degrade cell wall NSP, esp. arabino-xylans, to smaller xylo-oligomers. The latter are prebiotic fermentable oligosaccharides that support growth of beneficial gut microflora and suppress growth of pathogenic bacteria. Despite considerable research, Xylanase and other carbohydrases only slightly improve energy release from DDGS, Midds. NPB interest in by-products, such as DDGS, is due to their often equivalent to greater gross energy than corn, but their lower NE. Multiple carbohyrases improved the value of high NDF ingredients, but appears not equivalent to 1.50% fat, as advertised. Proteases have been difficult to prove effective to this point.